120 Gbit/s Over 500-km Using Single-Band Polarization-Multiplexed Self-Coherent Optical OFDM - Schmidt, Brendon J. C.; Zan, Zuraidah; Liang, B. Du; Lowery, Arthur J. (Institute of Electrical and Electronics Engineers, 2010)
In this paper, we experimentally demonstrate a single-band self-coherent polarization-multiplexed optical orthogonal frequency-division multiplex system with a raw data rate of 120 Gbit/s. The transmitter uses a novel RF structure that eliminates the need for RF mixers and optical filters. The receiver uses a novel architecture where the optical carrier is filtered and amplified for self-coherent detection. The receiver is polarization diverse and allows for the usual frequency guard band between the carrier and the sideband to be reduced in width, thus increasing spectral efficiency. Using two commercial 20 GS/s arbitrary-waveform generators to generate a single information-carrying band per polarization, we achieve a raw data rate of 120 Gbit/s over 500 km of standard single-mode fiber.